A Fresh View on Lymph Node Organogenesis. Issue 10 (October 2018) - Onder, Lucas; Ludewig, Burkhard
Abstract : Lymph nodes (LNs) are strategically positioned outposts of the immune system that underpin regional immune surveillance. The current model describing LN formation in mice is based on a two cell-type interaction scheme with lymphoid tissue inducer cells regulating the activation of mesenchymal lymphoid tissue organizer cells. We highlight here the key role of lymphatic endothelial cells during the initiation of LN formation. The involvement of lymphatic endothelial cells as an additional organizer cell type in LN organogenesis unveils multiple control levels that govern the generation of lymphoid organs. Moreover, the linkage between lymphangiogenic and lymphvasculogenic processes and guidance of the accumulation and activation of lymphoid tissue inducer cells in the embryo suggests that LN formation may be driven on demand by developing organ systems. Highlights: Mammalian LN development is part of organ-specific lymphatic vasculature formation. Embryonic lymphatic endothelial cells act as primary lymphoid tissue organizer (LTo) cells during the initiation of murine LN formation. The trafficking of lymphoid tissue inducer (LTi) cells can be registered by lymphatic endothelial LTo cells at the main lymphatic vessel junctions in mice. LN formation might potentially emerge as a consequence of the swarming behavior of LTi cells. Enhanced lymphangiogenesis and elevated trafficking of lymphocytes may function to stimulate de novo generation of LNs in humans.